Using automated glycan assembly (AGA) for the practical synthesis of heparan sulfate oligosaccharide precursors. Issue 7 (13th December 2018) - Budhadev, Darshita; Saxby, Karinna; Walton, Julia; Davies, Gideon; Tyler, Peter C.; Schwörer, Ralf; Fascione, Martin A.
Abstract : Herein we report synthesis of complex heparan sulfate oligosaccharide precursors by automated glycan assembly using disaccharide donor building blocks. Abstract : Herein we report synthesis of complex heparan sulfate oligosaccharide precursors by automated glycan assembly using disaccharide donor building blocks. Rapid access to a hexasaccharide was achieved through iterative solid phase glycosylations on a photolabile resin using Glyconeer™, an automated oligosaccharide synthesiser, followed by photochemical cleavage and glycan purification using simple flash column chromatography.